Implementation of the MARCO Application as a Digital Customer Relationship Management Strategy at PT Terminal Teluk Lamong - Acep Samsudin; Novenya Rahmadani (International Journal of Social, Economic, and Business, 2025)
This study aims to analyze the implementation of the MARCO application as a digital Customer Relationship Management (CRM) strategy to improve the business performance of PT Terminal Teluk Lamong. A descriptive qualitative approach was used, with data collection techniques including interviews, observation, documentation, and literature review. The research findings show that the MARCO application helps the company enhance operational efficiency, customer satisfaction and loyalty, as well as revenue growth. MARCO serves as a digital solution capable of systematically recording, monitoring, and following up on customer feedback. However, some challenges remain, such as the lack of system integration across internal units. This study concludes that MARCO plays a strategic role in supporting CRM and strengthening the business performance of a digitally-driven port company.